1981
DOI: 10.1037/0021-843x.90.6.554
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive activity and suggestions for analgesia in the reduction of reported pain.

Abstract: Pain magnitude and pain tolerance for arm immersion in ice water were assessed during a baseline and posttest session. Before the posttest half the subjects received (and half did not receive) an analgesia suggestion. On the basis of their written testimony, subjects were classified as having either predominantly coped (e.g., imagined events inconsistent with pain; made positive self-statements) or predominantly exaggerated (e.g., worried about and exaggerated the noxious aspects of the situation) during each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Sullivan et al (18) have suggested that catastrophizing is a temporally stable variable primarily based on earlier research with undergraduate samples. Others have indicated that individuals may develop enduring schemas regarding the threat of pain and their ability to effectively cope with the pain (44,45). Catastrophizing post-TKA may be better understood as a negative cognitive appraisal process that fluctuates with the amount of pain that is experienced because preoperative catastrophizing does not predict future pain occurrence in this sample (44).…”
Section: Catastrophizing and Tka Painmentioning
confidence: 95%
See 1 more Smart Citation
“…Sullivan et al (18) have suggested that catastrophizing is a temporally stable variable primarily based on earlier research with undergraduate samples. Others have indicated that individuals may develop enduring schemas regarding the threat of pain and their ability to effectively cope with the pain (44,45). Catastrophizing post-TKA may be better understood as a negative cognitive appraisal process that fluctuates with the amount of pain that is experienced because preoperative catastrophizing does not predict future pain occurrence in this sample (44).…”
Section: Catastrophizing and Tka Painmentioning
confidence: 95%
“…It is likely that such a range restriction reduces the variance accounted for in the prospective analyses. As an alternative line of evidence suggests, catastrophizing may be more appropriately considered as a readily modifiable, situation-specific cognitive style (27,45). This suggestion, that catastrophizing is acquiescent to modification, is interesting.…”
Section: Preoperative Catastrophizingmentioning
confidence: 99%
“…in the absence of intervention, may be markedly stable overtime (Keefe et al, 1989). However, a number of investigators have demonstrated that catastrophizing can be significantly reduced or eliminated by interventions that foster the use coping strategies (Spanos et al, 1979(Spanos et al, , 1981Vallis, 1984). In Study 2, no interventions were used to modify level of catastrophizing, and it was predicted that PCS scores would remain stable over a 6-week period.…”
mentioning
confidence: 99%
“…Still later Kirmayer writes the following: "In his laboratory Spanos is able to ignore or minimize the most salient features of hypnosis: the spontaneous absorptive and imaginative experiences of hypnotically talented subjects and the sense of involuntariness." Yet for almost two decades I have been heavily involved in developing standardized procedures for the assessment of (1) experienced involuntariness (Spanos, Radtke, Hodgins, Stam & Bertrand 1983) and of (2) absorption in suggestion-related imaginings and in studying (3) individual differences in subjects' imaginal responses to suggestions (e.g., Spanos & McPeake 1977), (4) subjects' "spontaneous" use of imaginal strategies (e.g., Spanos, Brown, Jones & Homer 1981), (5) the relationships between absorption and hypnotic susceptibility (e.g., Spanos & Moretti, in press), and (6) the relations between imaginal activity and the experience of responding involuntarily (e.g., Spanos 1971;Spanos, Cobb & Gorassini 1985).…”
Section: Continuing Commentarymentioning
confidence: 99%